Evolution of fruit development genes in flowering plants - Pabón-Mora, Natalia; Wong, Gane Ka-Shu; Ambrose, Barbara A. (Frontiers in Plant Science, 2014)
The genetic mechanisms regulating dry fruit development and opercular dehiscence have been identified in Arabidopsis thaliana. In the bicarpellate silique, valve elongation and differentiation is controlled by FRUITFULL (FUL) that antagonizes SHATTERPROOF1-2 (SHP1/ SHP2) and INDEHISCENT (IND) at the dehiscence zone where they control normal lignification. SHP1/2 are also repressed by REPLUMLESS (RPL), responsible for replum formation. Similarly, FUL indirectly controls two other factors ALCATRAZ (ALC) and SPATULA (SPT) that function in the proper formation of the separation layer. FUL and SHP1/2 belong to the MADS-box family, IND and ALC belong to the bHLH family and RPL belongs to the homeodomain family, all of which are large transcription factor families. These families have undergone numerous duplications and losses in plants, likely accompanied by functional changes. Functional analyses of homologous genes suggest that this network is fairly conserved in Brassicaceae and less conserved in other core eudicots. Only the MADS box genes have been functionally characterized in basal eudicots and suggest partial conservation of the functions recorded for Brassicaceae. Here we do a comprehensive search of SHP, IND, ALC, SPT and RPL homologs across core-eudicots, basal eudicots, monocots and basal angiosperms. Based on gene-tree analyses we hypothesize what parts of the network for fruit development in Brassicaceae, in particular regarding direct and indirect targets of FUL, might be conserved across angiosperms.